2016
DOI: 10.1097/rlu.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aggressiveness of Breast Cancer Using Simultaneous 18F-FDG-PET and DCE-MRI

Abstract: Purpose To investigate the feasibility of using simultaneous breast MRI and PET to assess the synergy of MR pharmacokinetic and fluorine-18 fluorodeoxyglucose (18F-FDG) uptake data to characterize tumor aggressiveness in terms of metastatic burden and Ki67 status. Methods Twelve consecutive patients underwent breast and whole body PET/MRI. During the MR scan, PET events were simultaneously accumulated. MR contrast kinetic model parametric maps were computed using the extended Tofts model, including the volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In that study, K trans and SUV max correlated positively with metastatic disease, whereas K ep correlated negatively. Similarly, tumors with higher levels of Ki67, a marker for cell proliferation, showed a significantly greater K trans compared with tumors with lower levels of Ki67 . Data like these suggest the potential for K trans and SUV max to suggest patients in whom whole‐body imaging should be performed to assess for metastatic disease.…”
Section: Index Lesion Evaluationmentioning
confidence: 79%
See 2 more Smart Citations
“…In that study, K trans and SUV max correlated positively with metastatic disease, whereas K ep correlated negatively. Similarly, tumors with higher levels of Ki67, a marker for cell proliferation, showed a significantly greater K trans compared with tumors with lower levels of Ki67 . Data like these suggest the potential for K trans and SUV max to suggest patients in whom whole‐body imaging should be performed to assess for metastatic disease.…”
Section: Index Lesion Evaluationmentioning
confidence: 79%
“…Margolis et al evaluated perfusion data K trans , K ep , and V e , and 18 F‐FDG PET data standardized uptake value (SUV) and metabolic tumor volume (MTV) in breast cancer patients with and without metastases . In that study, K trans and SUV max correlated positively with metastatic disease, whereas K ep correlated negatively.…”
Section: Index Lesion Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy regimens varied accordingly with the heterogeneity in histology and prognostic factors of the tumor and included hormone therapy and cytotoxic treatment. Results from the whole body PET/MR evaluation (33) or local DCE-MRI (34) of these patients have been recently reported and in some cases provided the metastatic burden assessment considered in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…This group also looked at recurrence-free survival and found that patients with more heterogeneous FDG uptake had worse recurrence-free survival than patients with less heterogeneous tumors. 45 In a smaller study, Margolis and colleagues 47 found that metabolic tumor volume inversely correlated with Kep and K trans and that metastatic burden correlated positively with K trans and SUVmax and negatively with Kep.…”
Section: Mr Imaging and Pet In Localized Breast Examinationsmentioning
confidence: 98%